Imposing Compulsory Rugby Union on Schoolchildren: An Analysis of English State-Funded Secondary Schools - White, Adam John; Batten, John; Howarth, Nathan E.; Magrath, Rory; Piggin, Joe; Millward, Pete; Parry, Keith D.; Lang, Melanie; Bullingham, Rachael; Pearce, Alan J.; Morales, Luis; Turner, Gary; et al. (Frontiers in Sports and Active Living, 2022)
Objective: to establish the extent to which Rugby Union was a compulsory physical education activity in state-funded secondary schools in England and to understand the views of Subject Leaders for Physical Education with respect to injury risk. Method: a cross-sectional research study using data obtained under the Freedom of Information Act (2000) from 288 state-funded secondary schools. Results: Rugby Union was delivered in 81% (n = 234 of 288) of state-funded secondary school physical education curricula, including 83% (n = 229 of 275) of state-funded secondary school boys’ and 54% (n = 151 of 282) of girls’ physical education curricular. Rugby Union was compulsory in 91% (n = 208 of 229) of state-funded secondary schools that delivered it as part of the boys’ physical education curriculum and 54% (n = 82 of 151) of state-funded secondary schools that delivered contact Rugby Union as part of the girls’ physical education curriculum. Subject Leaders for Physical Education also perceived Rugby Union to have the highest risk of harm of the activities they delivered in their school physical education curriculum. Conclusion: Notwithstanding discussions of appropriate measures (i.e., mandatory concussion training, Rugby Union specific qualifications and CPD) to reduce injury risk, it is recommended that Rugby Union should not be a compulsory activity given that it has a perceived high risk of injury and is an unnecessary risk for children in physical education.